Phytoremediation of metals, metalloids, and radionuclides - McGrath, S.P.; Zhao, J.; Lombi, E. (Advances in Agronomy, 2002)
Phytoremediation is a developing technology that can potentially address the problems of contaminated agricultural land or more intensely polluted areas affected by urban or industrial activities. Three main strategies currently exist to phytoextract inorganic substances from soils using plants:(1) use of natural hyperaccumulators; (2) enhancement of element uptake of high biomass species by chemical additions to soil and plants; and (3) phytovolatilization of elements, which often involves alteration of their chemical form within the plant prior to volatilization to the atmosphere. Concentrating on the techniques that potentially remove inorganic pollutants such as Ni, Zn, Cd, Cu, Co, Pb, Hg, As, Se, and radionuclides, we review the progress in the understanding of the processes involved and the development of the technology. This includes the advances made in the study of the physiology and biochemistry of metal uptake, transport and sequestration by hyperaccumulator plants, as well as the investigation of the processes occurring in soil and plant systems subject to the chemical enhancement approach. Enough work has been carried out in the last decade to allow some assessment of the situations and elements in which phytoremediation is likely to be most successful. However, we also identify where there is lack of knowledge. Finally, the likely future directions for research and application are discussed.